2022
DOI: 10.1186/s12909-022-03852-3
|View full text |Cite
|
Sign up to set email alerts
|

Artificial intelligence in medical education: a cross-sectional needs assessment

Abstract: Background As the information age wanes, enabling the prevalence of the artificial intelligence age; expectations, responsibilities, and job definitions need to be redefined for those who provide services in healthcare. This study examined the perceptions of future physicians on the possible influences of artificial intelligence on medicine, and to determine the needs that might be helpful for curriculum restructuring. Methods A cross-sectional mul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
86
0
3

Year Published

2023
2023
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 136 publications
(95 citation statements)
references
References 29 publications
6
86
0
3
Order By: Relevance
“…According to a survey of more than 3,000 medical students in different countries, their main concern (amongst almost 50% of all respondents) related to the entry of AI into medicine is that it will lead to higher unemployment among medical staff [3]. It is important to note that AI is already actively used in medicine.…”
Section: Resultsmentioning
confidence: 99%
“…According to a survey of more than 3,000 medical students in different countries, their main concern (amongst almost 50% of all respondents) related to the entry of AI into medicine is that it will lead to higher unemployment among medical staff [3]. It is important to note that AI is already actively used in medicine.…”
Section: Resultsmentioning
confidence: 99%
“…Although the integration and teaching of AI as part of medical education have been of increased scientific interest in recent years, further highlighting the need for early and adequate education of medical students, the available research is still limited [ 6 , 8 , 19 , 34 ]. The comparability and practical implications of current research are further limited not only due to a lack of standardization in terms of the definition of AI and possible teaching content but rather due to differences in the structure of medical education between different countries in general [ 19 ].…”
Section: Discussionmentioning
confidence: 99%
“…education observed in the present study is also in line with prior studies among medical and dental students, where 71-85% of the respondents indicated a positive attitude towards AI teaching. [19][20][21][36][37][38] Of particular interest, a comprehensive 2021 study by Bisdas et al…”
Section: Discussionmentioning
confidence: 99%